DYNAMICS OF ACTIVITY OF SOME COMPONENTS OF COMPLEMENT IN TREATMENT OF ATOPIC DERMATITIS IN CHILDREN - S. S. Andina; A. M. Bichucher; N. V. Gora; L. V. Kozlov; O. V. Logunov; O. A. Bashkina; O. V. Rubalsky; A. V. Aleshkin (Детские инфекции (Москва))
The article describes immunoassay methods of determining the functional activity of the components C3 and C9 and C1 inhibitor for diagnostic and prognostic purposes in the treatment of patients. The activity of these components, as well as the activity and the amount of C1 inhibitor in the blood serum of children aged 6 months to 18 years suffering from atopic dermatitis have been analyzed before and after treatment to determine the involvement of the complement system in the pathogenesis of this disease. The developed methods of enzyme immunoassay for determination of the functional components of the complement system have shown high sensitivity and reliability. The activity of C9 component involved in the membrane attack of the complement was significantly below normal in children with atopic dermatitis. That indicates the involvement of membrane attack complex components in the skin necrotic processes. Component C3 activity is also reduced. C3 is the key component of the activation cascade involved in the inflammatory processes. Specific activity of C1 inhibitor increased before and during the treatment, indicating an increased biosynthesis of this acute phase protein. Positive tendency towards the normalization of the status of complement after treatment has been observed. Data obtained in this study indicate the involvement of complement system in the pathological process of atopic dermatitis in children.